Sistem Monitoring Pertumbuhan Tanaman Sawi Menggunakan Artificial Intelligence Pada Aquaponik - deviana, lyla putri; Styawati, Styawati (Politeknik Harapan Bersama, 2024)
Modern agriculture increasingly relies on technology to increase efficiency and productivity. Aquaponics, a sustainable farming method that combines fish and plant farming, has emerged as one promising approach. To maximize yield in an aquaponics system, monitoring plant growth becomes very important. In this context, Artificial Intelligence (AI) offers innovative solutions to monitor and optimize plant growth in realtime. AI-based aquaponics technology is designed portably so that it allows people to grow crops inside and outside the home. AIbased aquaponics technology uses a camera that functions to monitor plants in real-time. The data on the camera will be processed and analyzed by the AI system so that automatic monitoring of the plant growth environment in the system can be carried out. Where will output results that show whether the leaves are still fresh, immediately wither Using CNN's deep learning method, this technology contributes to sustainable food production with higher efficiency in managing resources. This system can increase productivity and strengthen food security in the face of future challenges. This aquaponics technology can make a significant contribution to the development of sustainable agriculture and can provide guidance and inspiration for agricultural and food industry players. By optimizing food production through AI-based aquaponics systems, communities can face global food security challenges and move towards more environmentally friendly, efficient, and sustainable solutions for the future.